PENGEMBANGAN BANK SOAL TEMATIK BERBASIS HIGHER ORDER THINKING SKILLS (HOTS) DI SEKOLAH DASAR - Dina Fadilah; Musabihatul Kudsiah; Novia Karlinda; Haifaturrahmah (JIPD (Jurnal Inovasi Pendidikan Dasar), 2021)
This study aims to determine how to develop a Higher Order Thinking Skills/ HOTS based question bank in elementary schools and to find out the results of developing a HOTS-based question bank. This research is a research and development (research and development). The method used in this research is to refer to the 4D learning model by Thiagarajan, Semmel and Semmel which consists of 4 stages of development, namely defining, designing, developing, and disseminating. The item validation sheet is used to determine the validity of the product. Based on the results of the quantitative analysis of HOTS items, it shows that out of 100 items, 90 items are eligible to be included in the question bank by obtaining data from the validation results of the expert team of 0.75 (high criteria), reliability of 0.90 (very high criteria), the mean differe nce of each is 0, 6 (good criteria), and the average level of difficulty is 0.4 (moderate criteria).